2010
DOI: 10.1117/1.3474978
|View full text |Cite
|
Sign up to set email alerts
|

JPEG2000 encoding of images with NODATA regions for remote sensing applications

Abstract: The aim of this work is to, within the JPEG2000 framework, enhance the coding performance obtained for images that contain regions without useful information, or without information at all, here named as NODATA regions. In Geographic Information Systems (GIS) and in Remote Sensing (RS), NODATA regions arise due to several factors, such as geometric and radiometric corrections, atmospheric events, the overlapping of successive layers of information, etc. Most coding systems are not devised to consider these reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Besides the above mentioned methods, there were also many others which have evaluated compression efficiency against the specific remote sensing tasks like classification [35,43,55,[57][58][59][60], image segmentation [61], atmospheric parameter retrieval [14,62], spectral unmixing [63], endmember extraction [64], vegetation [53,54] and spectral [65] indices computation, and biophysical variables estimation [66]. In [59] it was concluded that in the context of the general applications it is hard to define optimal level of image quality that should be preserved by the lossy compression.…”
Section: Applications Oriented Lossy Compression-related Workmentioning
confidence: 99%
“…Besides the above mentioned methods, there were also many others which have evaluated compression efficiency against the specific remote sensing tasks like classification [35,43,55,[57][58][59][60], image segmentation [61], atmospheric parameter retrieval [14,62], spectral unmixing [63], endmember extraction [64], vegetation [53,54] and spectral [65] indices computation, and biophysical variables estimation [66]. In [59] it was concluded that in the context of the general applications it is hard to define optimal level of image quality that should be preserved by the lossy compression.…”
Section: Applications Oriented Lossy Compression-related Workmentioning
confidence: 99%
“…Defining the nodata value as −999 is not arbitrary because nodata values that are defined too far from the valid data range can negatively affect normalization compression procedures. 38 Consistent treatment of nodata values is one of the keys to performing correct image processing and subsequent data analysis.…”
Section: Image Processingmentioning
confidence: 99%